Molecular mechanism investigation on the interaction of Clothianidin with human serum albumin. Issue 5 (28th May 2019) - Wang, Kun; Wang, Zhong; Xie, Yanhua; Xue, Xinguang; Tang, Si-Fu; Hou, Xiaomin
Abstract: With the widespread application of neonicotinoid insecticides, Clothianidin has received much attention due to the potential harm to human health and ecological environment. However, the mechanism of Clothianidin's underlying toxicity to organisms remains unclear. In this work, the interaction between Clothianidin and human serum albumin was investigated and the intrinsic fluorescence of human serum albumin got quenched via static mechanisms upon the addition of Clothianidin. The binding constants between Clothianidin and human serum albumin at three different temperature were obtained to be 3.543 × 10 4, 2.995 × 10 4, and 2.490 × 10 4 M −1, respectively. Based on the van't Hoff equation, the thermodynamic parameters, Δ H 0 and Δ S 0 were estimated to be −53.885 KJ mol −1 and −110.535 J mol −1 K −1, respectively. A single binding site was predicted from the binding constants at different temperatures by multiple spectroscopic techniques and the negative values of Δ H 0 and Δ S 0 indicated the binding of human serum albumin with Clothianidin was driven by hydrogen bonds or van der Waals forces. Furthermore, the loose and unfolded secondary structure of human serum albumin along with the addition of clothianidin had been observed through ultraviolet-visible absorption and circular dichroism spectra. In addition, it was also found that Clothianidin had polar effects of structural microenviroment not only on Trp but also Tyr residues from synchronous fluorescence analysis. This study illuminates the molecular mechanism of the interaction between human serum albumin and clothianidin for the first time and helps to construct a specific pesticide biosensor system of human health.